Models of idealized films and optimal networks relations between the problems and simulation results - Šaltenis, Vydūnas (Lietuvos matematikos rinkinys, 2002)
Simulation of idealized films under complex constraints is an instrument of investigating length-minimizing curves. If we select the proper evolution of the curves, their shapes may approach to the solution of some combinatorial problems. The simulation of wet films was used in algorithms and software for solving the Steiner problem. The results of the computational experiments are presented.